2007
DOI: 10.1111/j.1471-0374.2007.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Women Working Worldwide: transnational networks, corporate social responsibility and action research

Abstract: In this article we trace the history of a new form of labour internationalism that emerged in support of women workers ' organizations, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 12 publications
0
50
0
2
Order By: Relevance
“…Retailer codes of conduct and broader international multi-stakeholder schemes and accreditations seek to address the negative outcomes of globalisation in terms of labour standards, by imposing various conditions upon the lead firm and its suppliers (Hale and Wills, 2007;Hughes et al 2007; 2008; Ruwanpura and Wrigley, 2011). CSR may thus be perceived as a form of privatised governance in the absence of necessarily tight national forms of regulation (Christopherson and Lillie, 2005;Tallontire, 2007;Mayer and Pickles, 2010), though its uneven implementation remains a concern (Ruwanpura, 2013).…”
Section: Corporate Social Responsibility In Global Garment Productionmentioning
confidence: 99%
“…Retailer codes of conduct and broader international multi-stakeholder schemes and accreditations seek to address the negative outcomes of globalisation in terms of labour standards, by imposing various conditions upon the lead firm and its suppliers (Hale and Wills, 2007;Hughes et al 2007; 2008; Ruwanpura and Wrigley, 2011). CSR may thus be perceived as a form of privatised governance in the absence of necessarily tight national forms of regulation (Christopherson and Lillie, 2005;Tallontire, 2007;Mayer and Pickles, 2010), though its uneven implementation remains a concern (Ruwanpura, 2013).…”
Section: Corporate Social Responsibility In Global Garment Productionmentioning
confidence: 99%
“…MSIs which enjoyed the attention of scholars are the Clean Cloth Campaign (CCC), the Social Accountability 8000 (SA8000), the Fair Labour Association (FLA), and the Fair Wear Foundation (FWF) [59,[71][72][73][74]. Although some studies describe the important role of unions in improving labor standards [68,[75][76][77][78], no further study has been found that clearly analyzed the unions' influences on SSCM. Also, public or governmental regulations as drivers have found scant attention since 2005.…”
Section: Driversmentioning
confidence: 99%
“…Freise und Seuring [3] x 0 x Towers et al [85] x x 0 Hale und Wills [77] x x 0 O'Rourke [71] 0 x x Lueg et al [66] x x 0 Shaw et al [84] x 0 x Park-Poaps und Rees [65] x 0 x Kozlowski et al [99] 0 0 0 Milne et al [67] x x 0 Sancha et al [13] 0 0 0 Bhaduri & Ha-Brookshire [100] x 0 0 Egels-Zandén und Hyllman [76] x x 0 Dargusch und Ward [90] 0 0 0 Curwen et al [92] 0 0 0 Carrigan et al [82] x 0 x Burchielli et al [75] x x 0 Ansett [86] 0 x 0 Goworek [93] 0 0 0 Svensson [95] x 0 0 Iwanow et al [83] x 0 x Börjeson et al [96] 0 0 0 Giannakis & Papadpoulos [24] 0 0 0 de Brito et al [43] x x 0 Perry et al [101] 0 0 0 Locke, Qin et al [97] 0 x 0…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The public aims of CoCs are to improve the material welfare of workers in contract suppliers' factories, to curb or remove arbitrary and coercive exercises of managerial power and authority, and to substantiate workers' human rights, such as freedom of association and gender rights. A snap verdict of CoC effectiveness in these areas would be largely negative (Hale and Wills, 2007;Raworth and Coryndon, 2004;War On Want, 2008). With ineffective monitoring and unauthorized subcontracting, brands and retailers often fail to track their producers and hence enforce CoCs -not only at factories in developing countries (Level Works, 2009), but even in the heartland of some brands' headquarters, such as the UK (Dispatches, 2010).…”
mentioning
confidence: 99%
“…A snap verdict of CoC effectiveness in these areas would be largely negative (Hale and Wills, 2007;Raworth and Coryndon, 2004;War On Want, 2008). With ineffective monitoring and unauthorized subcontracting, brands and retailers often fail to track their producers and hence enforce CoCs -not only at factories in developing countries (Level Works, 2009), but even in the heartland of some brands' headquarters, such as the UK (Dispatches, 2010).…”
mentioning
confidence: 99%